HIPERTEXTOS Y MAPAS CONCEPTUALES EN AMBIENTES DE APRENDIZAJE COLABORATIVO - Fonseca Ramírez, Oscar Hernán (Tecné, Episteme y Didaxis: TED, 2000)
Report of investigation for determine the incidence in the retention of concepts of two experimental conditions: first between the students who construct conceptual maps against which they observe the simulation of the map constructed by an expert and the second social condition of work: colaborativo against individual, of this combination four experimental groups determined themselves. The students made the study of the concept “Model of the Atom” in a hypertextual software.